Plants Biodiversity of Jobolarangan Forest Mount Lawu: 1. Cryptogamae - AHMAD DWI SETYAWAN; SUGIYARTO SUGIYARTO (Society for Indonesian Biodiversity, 2001)
The objectives of the research were to make: (1) a list of Cryptogamic plants at Jobolarangan forest in mount Lawu,and (2) the actual condition of biodiversity conservation of the plants. All Cryptogamic plants on the forest were studied. The procedures of data collection were including species collection in the field, make up herbaria, observation of flora vegetation using transect method, morphology observation in the laboratory, and interview to residents and government administrations. The results showed that in the forest were found 77 species Cryptogamic plants, consisting of 27 species of fungi, 5 species of lichens, 20 species of Bryophyta and 25 species of Pterydophyta. Government and residents had successfully conserved the forest; however fire and illegal logging damaged another part.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: biodiversity, Cryptogamic plants, Jobolarangan, mount Lawu